Equivalence of Definitions of Hyperbolic Cosecant
Jump to navigation
Jump to search
Theorem
The following definitions of the concept of Hyperbolic Cosecant are equivalent:
Definition 1
The hyperbolic cosecant function is defined on the complex numbers as:
- $\csch: X \to \C$:
- $\forall z \in X: \csch z := \dfrac 2 {e^z - e^{-z} }$
where:
- $X = \set {z: z \in \C, \ e^z - e^{-z} \ne 0}$
Definition 2
The hyperbolic cosecant function is defined on the complex numbers as:
- $\csch: X \to \C$:
- $\forall z \in X: \csch z := \dfrac 1 {\sinh z}$
where:
- $\sinh$ is the hyperbolic sine
- $X = \set {z: z \in \C, \ \sinh z \ne 0}$
Proof
\(\ds \forall z \in \set {z \in \C: \ e^z - e^{-z} \ne 0}: \, \) | \(\ds \) | \(\) | \(\ds \frac 2 {e^z - e^{-z} }\) | Definition 1 of Hyperbolic Cosecant | ||||||||||
\(\ds \forall z \in \set {z \in \C: \ \frac {e^z - e^{-z} } 2 \ne 0}: \, \) | \(\ds \) | \(=\) | \(\ds 1 / \frac {e^z - e^{-z} } 2\) | |||||||||||
\(\ds \forall z \in \set {z \in \C: \ \sinh z \ne 0}: \, \) | \(\ds \) | \(=\) | \(\ds 1 / \sinh z\) | Definition 2 of Hyperbolic Cosecant |
$\blacksquare$